2018
DOI: 10.5582/ddt.2018.01001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of rectal feces storage condition by a point-of-care pocket-size ultrasound device for healthy adult subjects: A preliminary study

Abstract: The aim of this study was to assess rectal feces storage condition by a pocket-size ultrasonography (PUS) in healthy adults so as to define normal rectal defecation desire. Participants were first assessed rectum by PUS imaging immediately after defecation desire (pre-defecation). Nurses checked the amount and quality of the participants' feces using King's Stool Chart and Bristol stool scale. Finally, PUS was performed for defecation with no defecation desire (post-defecation). Pre-defecation PUS detected hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 21 publications
(33 reference statements)
2
33
0
2
Order By: Relevance
“…Furthermore, we confirmed that the said hyperechoic area can be observed in the rectum of patients with functional constipation . Furthermore, we showed that the existence of hard stool can be identified by observing the strong hyperechoic area with acoustic shadow in the rectum using handheld US …”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…Furthermore, we confirmed that the said hyperechoic area can be observed in the rectum of patients with functional constipation . Furthermore, we showed that the existence of hard stool can be identified by observing the strong hyperechoic area with acoustic shadow in the rectum using handheld US …”
Section: Introductionsupporting
confidence: 74%
“…All US observations were carried out by visiting nurses who completed an educational program from February 2018 to April 2018 on colorectal observation by US for the evaluation of functional constipation (under review). US was carried out using the SonoSite iViz handheld US system (FUJIFILM SonoSite, Bothell, WA, USA) with a convex (2–5 MHz) sector probe (1–5 MHz), as reported previously . Gain and image depth were adjusted as necessary.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations